Implementation of ESP8266 and Turbidity Sensor in Water Turbidity Monitoring Model Using Fuzzy Tsukamoto - Daru, April Firman; Hirzan, Alauddin Maulana; Saputra, Ferry Bagus; Christianto, Paminto Agung (Journal of Advanced Computing Technology and Application (JACTA), 2024)
Drinking water quality is critical to public health. The 2020 Household Drinking Water Quality Study (SKAMRT) by the Indonesian Ministry of Health revealed that 70% of households consume water contaminated with bacteria, including Escherichia coli (E-coli). Although 93% of Indonesia’s population has access to adequate drinking water, only 11.9% meets safety standards. Regular quality testing, especially for turbidity, is essential with increasing water consumption. However, effective real-time monitoring remains a challenge. Advances in the Internet of Things (IoT) offer an efficient approach to water quality monitoring. This study develops an IoT-based system using the Fuzzy Tsukamoto method to monitor drinking water quality. The system integrates a turbidity sensor, NodeMCU ESP8266 microcontroller, and Firebase for data storage. Turbidity values ​​in Nephelometric Turbidity Unit (NTU) are processed by the Fuzzy Tsukamoto method to assess quality. The research results show that bottled drinking water with a turbidity level of 0.83 NTU meets the standards set by the Indonesian Minister of Health Regulation 492/Menkes/Per/IV/2010 and SNI 01-3553-2006, which means it is safe based on the turbidity level.